Predictive current control with instantaneous reactive power minimization for a four-leg indirect matrix converter - Garcia, Cristian F.; Rivera, Marco E.; Rodriguez, Jose R.; Wheeler, Patrick; Pena, Ruben S. (Institute of Electrical and Electronics Engineers, 2017)
This paper presents the experimental valida¬tion of a predictive current control strategy with minimiza¬tion of the instantaneous reactive input power for a Four-Leg Indirect Matrix Converter (4Leg-IMC). The topology includes an input matrix converter stage, which provides the dc voltage for a four-leg voltage source converter (VSC) output stage. The VSC’s fourth leg provides a path for the zero sequence load current. The control technique is based on a finite control set model predictive control (FCS-MPC) strategy, whereby the switching states for the input and out¬put converters are selected by evaluating a predictive cost function. This results in a simpler approach than that seen in other well-known modulation methods, such as three-dimensional space vector modulation (3D-SVM). Positive dc voltage, (a requirement for the safe operation of the IMC) and minimization of the instantaneous input reactive power are obtained, while maintaining good tracking of the load reference currents. Furthermore, soft switching is achieved by synchronizing the state changes in the input stage with the application of zero voltage space vectors in the inverter stage. The control strategy is experimentally verified using a laboratory prototype.